(untitled) (Albayan Scientific Journal, 2023)
The study aimed to measure the most important factors affecting wheat imports and know the causal relationship between the variables of the study during the period (1980-2014), and the results of the study found that the amount of imports in the previous year and the gross domestic product and the real exchange rate and the real import price have a significant impact on the amount of imports Of wheat commodity, and there is a statistically significant statistically significant relationship between the gross domestic product and the quantity of imports, as it was found that the error correction parameter reached its value (-0.30) Which means that it is negative and significant, therefore, any imbalance from the long-term equilibrium relationship between the variables of the model is adjusted annually by 30%, meaning that the imported quantity takes approximately 3 years towards its equilibrium value in the long term and it represents the speed of the adjustment of the equilibrium in the sense that the imbalance in the last period It is not entirely corrected during the year, as the study found that there is a long-term causation in one direction from the real import price to the amount of wheat imports, and there is a long-term causal relationship in one direction from the real import price to the real exchange rate of wheat, that is, the price Real import causes changes in the real exchange rate The study recommended restructuring the crops in Libya in favor of strategic crops, including wheat, and guaranteeing the purchase of wheat crops at attractive and previously known prices to farmers in order to encourage farmers to grow wheat crops, vertical and horizontal expansion in wheat production, developing storage policy and reducing waste